Natural convection of ferrofluids in partially heated square enclosures - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Al-Salem, Khaled (Elsevier, 2014)
In this study, natural convection of ferrofluid in a partially heated square cavity is numerically investigated. The heater is located to the left vertical wall and the right vertical wall is kept at constant temperature lower than that of the heater. Other walls of the square enclosure are assumed to be adiabatic. Finite element method is utilized to solve the governing equations. The influence of the Rayleigh number (10(4) <= Ra <= 5 x 10(5)), heater location (0.25H <= y(h) <= 0.75H), strength of the magnetic dipole (0 <= gamma <= 2), horizontal and vertical location of the magnetic dipole (-2H <= a <= -0.5H, 0.2H <= b <= 0.8H) on the fluid flow and heat transfer characteristics are investigated It is observed that different velocity components within the square cavity are sensitive to the magnetic dipole source strength and its position. The length and size of the recirculation zones adjacent to the heater can be controlled with magnetic dipole strength. Averaged heat transfer increases with decreasing values of horizontal position of the magnetic dipole source. Averaged heat transfer value increases from middle towards both ends of the vertical wall when the vertical location of the dipole source is varied. When the heater location is changed, a symmetrical behavior in the averaged heat transfer plot is observed and the minimum value of the averaged heat transfer is attained when the heater is located at the mid of vertical wall. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Magnetic dipole; Partial heating; Ferrofluid; Finite element method; Natural convection